Особливості формування маркетингової стратегії аграрних підприємств в умовах воєнного стану - Венгерова, Олена Василівна; Venherova, Olena (Запоріжжя : 2024, 2024)
UA: У статті розглянуто особливості формування маркетингової стратегії аграрних підприємств під час дії воєнного стану в Україні. Здійснено аналіз чинників макросередовища ринку аграрної продукції на основі DESTEP-аналізу. Розглянуто регіональні відмінності аграрних підприємств. Визначено особливості формування маркетингової стратегії аграрних підприємств в умовах воєнного стану. EN: Тask statement. The purpose of the article is to determine the peculiarities of forming a marketing strategy of agricultural enterprises under martial law. The method of analysis was used to assess the direct losses of the agro-industrial complex and land resources. With the help of a critical analysis, the scientific literature on the issues mentioned in the topic of the article was reviewed. Using the DESTEP analysis, the main factors of the macro-environment for agricultural enterprises of Ukraine are identified. Using the graphical method, the dynamics of changes in the volume of agricultural production in farms of all categories by region during the period of martial law is analyzed. Research results. The current conditions for the functioning of domestic agricultural enterprises are extremely difficult. This is evidenced by the estimates of direct costs of the agricultural sector presented in the article. At the same time, the government and international organizations are trying to support Ukrainian entrepreneurs by providing them with various types of financial assistance. The DESTEP analysis for Ukrainian agricultural enterprises showed that the war had a negative impact on the factors of the external marketing environment. It was found that direct losses from military operations in the agricultural sector are quite significant. The article analyzes the volumes of agricultural production by regions of Ukraine and concludes that the lowest production volumes are in the regions that suffered the most from the war. Conclusion. Different marketing strategies for certain groups of regions of Ukraine are proposed. The main features of the formation of the marketing strategy of agricultural enterprises during the period of martial law are formulated.
Features of developing marketing strategies for agricultural enterprises under wartime conditions
Keywords: маркетингова стратегія; аграрні підприємства; DESTEP-аналіз; сільськогосподарська продукція; інфраструктура; агропромисловий комплекс; marketing strategy; agricultural enterprises; DESTEP analysis; agricultural products; infrastructure; agro-industrial complex